حقوق الطفل في الاتفاقيات والمواثيق الدولية - دبابش, عبد الرؤوف (University of Eloued جامعة الوادي, 2017)
ما من أمانة في عنق العالم تفوق في قدسيتها الأطفال، وما من واجب يعلو في أهميته فوق احترام الجميع لحقوق الأطفال، لأن حمايتهم واحترام حقوقهم حمايةً لمستقبل البشرية بأسرها. وعلى الرغم من أن المجتمع الدولي لم يغفل الاهتمام بالأطفال وبحاجتهم للحماية والرعاية، إلا أننا ما نشاهده في أنحاء عديدة من العالم من انتهاكات لحقوق الأطفال تجعلنا نطرح العديد من التساؤلات حول وجود اتفاقيات دولية تعالج حقوق الطفل ومدى فعاليتها في هذه الحماية ؟ وتأتي هذه الورقة البحثية لتعالج موضوع حقوق الأطفال في ضوء الاتفاقيات والمواثيق الدولية. Abstract : There is no charge entrusted to the world more sacred than children, and there is no duty more significant than protecting and respecting children's rights, because protecting their rights is a protection of the future of all humanity. Although the international society did not ignore children and their needs for protection and care, but what we see in several parts of the world of infringements of children's rights makes us ask many questions about the existence of international treaties dealt with children's rights? and what is its efficiency in their protection . In this view this paper trait the topic of children’s rights in the light of International treaties and Charters
Rights of the Child in the international conventions and charters
مجلة البحوث والدراسات المجلد 14 العدد 01 جامعة الوادي
Keywords: الحقوق- الطفل- الاتفاقيات الدولية- القانون الدولي; rights - child - international conventions - international law